LITERACY AND NUMERACY SKILLS OF STUDENTS SD NEGERI BENER PEKALONGAN REGENCY BASED ON AKM IN 2021 - Dewi Nurul Kamal; Sumardi Sumardi (JME (Journal of Mathematics Education), 2023)
In 2021, the UN was abolished and then replaced with AKM. AKM aims to enable students to develop and actively participate in community life, including reading and mathematical literacy (numeracy). This research describes the literacy and numeracy skills of grade V students of SD Negeri Bener based on the results of an assessment-based minimum competencyassessment. This research uses qualitative methods. The research subjects used were the principal, class V teachers, grade V students, and the GLS Program Team of SD Negeri Bener, Wiradesa District, Pekalongan Regency, consistingof 8 people—data collection using in-depth interviews, observation, and documentation. The instruments of this study are recording devices and photo documentation. Data validity using triangulation and data analysis using interactive analysis models. Based on data analysis, it was found that students' literacy abilities based on the evaluation results in the AKM in November 2021 of 1.83 were included in the proficient category, which means that most students reached the minimum level of competence in literacy skills; this is evidenced that most grade V students can interpret indirect information in thetext and can draw conclusions from the text, As for students' numeracy ability of 1.63, included in the low category which means less than 50% of students achieve a minimum level of competence and less than 50% of students who can know, apply, count, and understand the concept of number domains; algebraic domains; geometry domain; Data and uncertainty domains.